1990
DOI: 10.1080/15287399009531453
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous absorption and skin decontamination of PCBS: In vitro studies with human skin and in vivo studies in the rhesus monkey

Abstract: Knowledge of the entry of polychlorinated biphenyls through the skin into the body and subsequent disposition aids estimation of potential for human health hazard. [14C]Aroclor 1242 and [14C]Aroclor 1254 were separately administered intravenously and topically to rhesus monkeys. Following iv administration, 30-d excretion was 39.4 +/- 5.9% urine and 16.1 +/- 0.8% feces (total 55.5 +/- 5.1%) for Aroclor 1242, and 7.0 +/- 2.2% urine and 19.7 +/- 5.8% feces (total 26.7 +/- 7.5%) for Aroclor 1254. Mineral oil and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 6 publications
1
27
0
Order By: Relevance
“…When rhesus monkeys were washed with various solvents, including soap and water, between 70 and 100% of Aroclor 1242 PCB was removed immediately following a 15 min skin application interval. The amount removed declined steadily with time, to where only 25-45% was being removed at 24 h postapplication (Wester et al, 1990). In an investigation of a hand-sampling method, where a hand is placed in a bag containing solvent and shaken, Fenske and Lu (1994) found that the removal efficiency of chlorpyrifos decreased from 43% immediately after exposure to 23% 1 h postexposure when a 10% isopropanol/distilled water solution was used as the solvent.…”
Section: Discussionmentioning
confidence: 99%
“…When rhesus monkeys were washed with various solvents, including soap and water, between 70 and 100% of Aroclor 1242 PCB was removed immediately following a 15 min skin application interval. The amount removed declined steadily with time, to where only 25-45% was being removed at 24 h postapplication (Wester et al, 1990). In an investigation of a hand-sampling method, where a hand is placed in a bag containing solvent and shaken, Fenske and Lu (1994) found that the removal efficiency of chlorpyrifos decreased from 43% immediately after exposure to 23% 1 h postexposure when a 10% isopropanol/distilled water solution was used as the solvent.…”
Section: Discussionmentioning
confidence: 99%
“…Skin samples collected from human cadavers and exposed in vitro to [ 14 C]-labelled Aroclor 1254 and Aroclor 1242 retained 43-44% of the administered dose over a 24-hour period when the mixtures were formulated in water (Wester et al, 1990(Wester et al, , 1993. A lower retention was observed when PCBs were formulated in mineral oil or adsorbed on contaminated soil.…”
Section: (C) Dermal Exposure (I)mentioning
confidence: 97%
“…In rhesus monkeys, percutaneous absorption in vivo of [ 14 C]-labelled Aroclor 1242 and Aroclor 1254 formulated in mineral oil was 20.4 ± 8.5% and 20.8 ± 8.3% of the administered dose, respectively, as determined by urinary and faecal excretion of radiolabel for 30 days after topical application (Wester et al, 1990).…”
Section: (Ii) Experimental Systemsmentioning
confidence: 99%
“…floors and walls) and the transfer of hazardous chemicals to human skin have been subject of major concerns to Howard and his research team, who, through numerous studies, have made important contributions in exploring human risk factors. Percutaneous absorption rates of pesticides, herbicides, and metals, such as chlordane [9], polychlorinated biphenyls (PCB) [10,11], 2,4-dichlorophenoxyacetic acid [12], arsenic [13], or cadmium [14] from contaminated soil and water were examined and compared using in vitro and in vivo methods, which included both animal and human models (table 1). From these results, Howard and his research team observed that skin acts as a lipid sink (stratum corneum) for the lipid-soluble contaminants while also serving as a transfer membrane for water and any contaminants dissolved within it.…”
Section: Percutaneous Absorptionmentioning
confidence: 99%
“…Decontamination, involving immediate removal of the contaminant from the skin performed in the most efficient manner, is the primary intervention needed following dermal exposures. For contaminants such as PCB [16] and glyphosate [10], the decontamination system most readily available on a practical basis is washing with water and soap. Timely use of flushing with copious amounts of water may physically remove the contaminant.…”
Section: Percutaneous Absorptionmentioning
confidence: 99%